Madwoman : a novel - Bieker, Chelsea, 1987- (Little, Brown and Company, 2024)
"Clove has gone to extremes to keep her past a secret. Thanks to her lies, she's landed the life of her dreams, complete with a safe husband and two adoring children who will never know the terror that was routine in her own childhood. If her buried anxiety threatens to breach the surface, Clove (if that is really her name) focuses on finding the right supplement, the right gratitude meditation. But when she receives a letter from a women's prison in California, her past comes screeching into the present, entangling her in a dangerous game with memory and the people she thought she had outrun. As we race between her precarious present-day life in Portland, Oregon and her childhood in a Waikiki high-rise with her mother and father, Clove is forced to finally unravel the defining day of her life. How did she survive that day, and what will it take to end the cycle of violence? Will the truth undo her, or could it ultimately save her?"--